COMPARISON OF ORAL NIFEDIPINE WITH INTRAVENOUS HYDRALAZINE FOR ACUTE HYPERTENSIVE EMERGENCIES OF PREGNANCY - Sabir, Samina; Yasmin, Sumaira; Abbas, Ghulam (Journal of Postgraduate Medical Institute, 2016)
Objective: To compare oral nifedipine with intravenous hydralazine in their rapidity to control hypertensive emergencies of pregnancy. Methodology: It was a comparative study, done in Gynae C unit, Lady Reading Hospital, Peshawar. The study included hundred patients with severe gestational hypertension â‰¥160/110 mmHg, randomly assigned to two groups (one given intravenous hydralazine and the other oral nifedipine) to achieve a blood pressure (BP) of â‰¤150/100 mmHg. BP was measured every 15 minutes for one hour. Side effects were noted in terms of maternal headache and hypotension and fetal heart rate. Results: Both drugs controlled BP in the given time period but hydralazine was more efficacious in terms of time and doses. The time required by hydralazine was 41.10±20.286 minutes as compared to nifidipine was 57.90±21.855 with a significant p value of 0.000. Few doses were required to control BP in case of hydralazine 2.74±1.35 as compared to nifidipine which was 3.86±1.45 with a significant "˜p' value of 0.000. Conclusion: The use of either hydralazine or nifidipine controlled BP in the target time period but hydralazine was more efficacious.